Enhancing okra performance through osmo-priming: Effects on germination, yield and quality - Navneet , K; Dipika , M; Arshdeep , S (Plant Science Today, 2025)
To assess the impact of various seed priming techniques on okra (Punjab Suhawani variety) performance. Seeds were sourced from Punjab Agricultural University; Ludhiana and the study was structured using a randomized block design (RBD) with three replications and eight treatments with plot size of 2.25×3.75m and followed spacing was 45×15 cm. The treatments included: T0 (un-primed) control, T1 (hydro-priming), T2 (osmo-priming with 5 % polyethylene glycol), T3 (osmo-priming with 3 % potassium chloride), T4 (halo-priming with 5 % potassium nitrate), T5 (halo-priming with 1.5 % magnesium nitrate), T6 (hormonal priming with 50 ppm gibberellic acid) and T7 (hormonal priming with 50 ppm naphthalene acetic acid). For each treatment, seeds were soaked in the prepared solutions for 24 hrs before sowing under the shade. The study assessed germination percentage (92.17 %), number of days to germination (5.06 days), seedling dry weight (30.10 mg), seedling length (23.66 cm), seedling Vigor index (2166.95 I and 2627.83 II), root and shoot ratio (0.69), number of pods plant-1 (12.28), individual pod weight (9.28 g), pod yield plot-1 (14.24 kg), pod yield plant-1 (14.29 g), pod yield tonnes hectare (12.89 t ha-1), chlorophyll index (52.13) and mucilage content (5.57 %) and iodine content (mg/kg). The highest germination rate and seedling performance were recorded in T2 (osmo-priming with 5 % PEG), followed closely by T6 (hormonal priming with 50 ppm GA3). In contrast, the unprimed seeds (T0) control showed no significant improvement in any of the evaluated parameters.